in vitro response of Colletotrichum to chitosan. Effect on incidence and quality on tropical fruit. Enzymatic expression in mango - Porfirio Gutierréz Martínez; Silvia Bautista-Baños; Guillermo Berúmen-Varela; Anelsy Ramos-Guerrero; Alba María Hernández-Ibañez (Acta Agronómica)
Colletotrichum is considered one of the fungal genera with the greatest diversity of species of phytopathogenic fungi and with a wide range of hosts including tropical fruits. In this study, the concentration of chitosan applied was a key factor in the in vitro inhibition of the three Colletotrichum isolates with the most sensitive being the one from banana. Germination was the development stage most affected by the application of this polymer. At the end of 10 days of storage, control of anthracnose in soursop, mango and banana fruit was considerable with the application of 1 % chitosan, with 80 to 100 % inhibition. Likewise, the ripening process of fruit with and without chitosan was generally similar. Activity of the peroxidase (POD) and polyphenol oxidase (PPO) enzymes was observed only in fruit of mango cv. 'Tommy Atkins,' inoculated and non-inoculated with C. gloeosporioides, the activity of both enzymes was higher in the chitosan treatments and the 1.0 % concentration was able to induce gene expression of POD and PPO, occurring until 24 h.